2002
DOI: 10.1099/00207713-52-4-1331
|View full text |Cite
|
Sign up to set email alerts
|

Marinitoga piezophila sp. nov., a rod-shaped, thermo-piezophilic bacterium isolated under high hydrostatic pressure from a deep-sea hydrothermal vent.

Abstract: . Growth is observed from pH 5 to pH 8, the optimum being at pH 6. The salinity range for growth is 10-50 g NaCl l N1 , the optimum being at 30 g l N1 . The isolate is able to grow on a broad spectrum of carbohydrates or complex proteinaceous substrates, and growth is stimulated by L-cystine and elemental sulfur. The GMC content of the genomic DNA is 29O1 mol %. According to phylogenetic analysis of the 16S rDNA gene, the strain is placed within the order Thermotogales, in the bacterial domain. On the basis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 47 publications
0
34
0
1
Order By: Relevance
“…Chemolithoautotrophic prokaryotes inhabiting deep-sea hot vents are represented by the anaerobic sulfur-reducing bacteria Desulfurobacterium thermolithotrophum (L'Haridon et al, 1998) and Nautilia lithotrophica (Miroshnichenko et al, 2002), the sulfur-and nitrate-reducing bacterium Caminibacter hydrogeniphilus (Alain et al, 2002a), the sulfate-reducing bacterium Thermodesulfobacterium hydrohenophilum (Jeanthon et al, 2002) and two microaerophilic bacteria of the recently described genus Persephonella (Götz et al, 2002), which are also able to reduce sulfur and nitrate. Chemoorganoheterotrophic species include aerobic thermophilic bacteria of the genera Bacillus and Thermus (Marteinsson et al, 1995(Marteinsson et al, , 1999) and the anaerobes Thermosipho melanesiensis (Antoine et al, 1997), Thermosipho japonicus (Takai & Horikoshi, 2000), Marinitoga camini (Wery et al, 2001), Marinitoga piezophila (Alain et al, 2002b) and Caminicella sporogenes (Alain et al, 2002c). All anaerobic organotrophic bacteria isolated so far from the deep-sea hydrothermal environment possess a fermentative type of metabolism; for some of these species, the ability to reduce sulfur or thiosulfate in the course of fermentation has been reported (Wery et al, 2001;Antoine et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Chemolithoautotrophic prokaryotes inhabiting deep-sea hot vents are represented by the anaerobic sulfur-reducing bacteria Desulfurobacterium thermolithotrophum (L'Haridon et al, 1998) and Nautilia lithotrophica (Miroshnichenko et al, 2002), the sulfur-and nitrate-reducing bacterium Caminibacter hydrogeniphilus (Alain et al, 2002a), the sulfate-reducing bacterium Thermodesulfobacterium hydrohenophilum (Jeanthon et al, 2002) and two microaerophilic bacteria of the recently described genus Persephonella (Götz et al, 2002), which are also able to reduce sulfur and nitrate. Chemoorganoheterotrophic species include aerobic thermophilic bacteria of the genera Bacillus and Thermus (Marteinsson et al, 1995(Marteinsson et al, , 1999) and the anaerobes Thermosipho melanesiensis (Antoine et al, 1997), Thermosipho japonicus (Takai & Horikoshi, 2000), Marinitoga camini (Wery et al, 2001), Marinitoga piezophila (Alain et al, 2002b) and Caminicella sporogenes (Alain et al, 2002c). All anaerobic organotrophic bacteria isolated so far from the deep-sea hydrothermal environment possess a fermentative type of metabolism; for some of these species, the ability to reduce sulfur or thiosulfate in the course of fermentation has been reported (Wery et al, 2001;Antoine et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Chemo-organotrophic thermophilic anaerobic bacteria isolated from these extreme environments include members of the order Thermotogales -Thermosipho melanesiensis (Antoine et al, 1997), Thermosipho japonicus (Takai & Horikoshi, 2000), Marinitoga camini (Wery et al, 2001a) and Marinitoga piezophila (Alain et al, 2002a) -as well as low-GC Gram-positive bacteria, such as Carboxydibrachium pacificum (Sokolova et al, 2001), Caloranaerobacter azorensis (Wery et al, 2001b) and Caminicella sporogenes (Alain et al, 2002b). In this article, we report the isolation and characterization of an anaerobic, moderately thermophilic, fermentative, endospore-forming micro-organism (strain SC 562 T ) belonging to a novel genus within the Bacillus-Clostridium subphylum of the Bacteria.…”
mentioning
confidence: 99%
“…A lot of bacteria able to use elemental sulfur in anaerobic respiration that have been isolated, including Caminibacter hydrogeniphilus (Alain et al, 2002a), Nautilia lithotrophica (Miroshnichenko et al, 2002), Desulfurobacterium thermolithotrophum (L'Haridon et al, 1998) and members of the genus Marinitoga (Alain et al, 2002b), are strictly anaerobic sulfur-reducing bacteria that live in deep-sea hydrothermal vents. Persephonella marina (Götz et al, 2002) and some strains in the e-Proteobacteria are facultatively anaerobic bacteria that are capable of reducing elemental sulfur.…”
Section: Differential Characteristics Of St55bmentioning
confidence: 99%
“…Culture-independent analyses based on a 16S rRNA gene clone sequence revealed that various micro-organisms inhabit such environments (Corre et al, 2001;Marteinsson et al, 1995;Takai & Horikoshi, 1999;Takai et al, 2001Takai et al, , 2003. In recent years, many novel thermophilic bacteria have been found in and around these hydrothermal vents (Alain et al, 2002b; Götz et al, 2002;Huber et al, 2002;Jeanthon et al, 2002; Miroshnichenko et al, 2003a, b;Nakagawa et al, 2003;Sako et al, 2003;Vetriani et al, 2004; Wery et al, 2001). , 2003b).…”
mentioning
confidence: 99%